On Collecting and Publishing the Albanian Oral Epic - Dushi, Arbnora (Approaching religion, 2014)
The aim of this paper is to examine how the Albanian epic known as the ‘Cycle of the Frontier Warriors’ has been presented in Albanian folklore collections. I will examine seven written versions of the song ‘The Wedding of Ali Bajraktari’, which belongs to this epic cycle. The ‘Cycle of the Frontier Warriors’, has been an object of collection since the beginning of the twentieth century. There are now dozens of volumes published, but the studies published to date concentrate on historical, thematic and comparative rather than contextual and textual issues.